Sufis in Western Society: Global Networking and Locality by Markus Dressler, Ron Geaves, and Gritt Klinkhammer, eds. (New York: Routledge, 2009. hbk. 207 pages) (American Journal of Islam and Society, 2011)
Contributors to the volume, Raudvere and Gaši, skillfully note that “cherished,unfamiliar or rejected—attitudes of Sufism are seldom neutral”(163). If one traces the evolution of Sufism to Western lands, this aneutralityis accentuated. Thus, Sufism in the West is understandably a growing ifunderstudied field. There is a dearth of surveys on the topic, and this makesadditional attention to global networking and locality especially welcome.The authors seek to challenge the romantic and literary biases of Orientalistscholarship, and the eleven chapters rise to the occasion because mostfocus on particular living Sufi communities.The opening chapters set the methodological tone. In the Introduction,the editors emphasize “Sufism as a lived religion” and they rightly acknowledgethat Sufism often acts “as a bridge between Eastern and Westernspiritual or mystical philosophy” (4). In Chapter 2, Peter Beyer usesthe term glocalization while arguing that “as globalized structures, religionsare no longer . . . regional affairs which can be understood primarilywith reference to a particular core region” (13). He narrates a story of twoCanadian Muslim women who might experience different kinds of beliefand practice on a spectrum of religiosity. Strangely, however, only oncein the article does he mention “Sufism,” and the false dichotomy “Sufi/scriptural,” which contrasts with the major concepts in the book, such asthe primacy of the Qur’an for many Sufis ...